2
$\begingroup$

I want to evaluate the following limit

$$\lim_{x\rightarrow1}{\frac{1+\log{x}-e^{x-1}}{(x-1)^2}}$$

I use L'Hospital's rule:

$$\lim_{x\rightarrow1}{\frac{\frac{1}{x}-e^{x-1}}{2(x-1)}}$$

Now, here my textbook applies the L'Hospital's rule again. What I instead did was proceeding this way:

$$\lim_{x\rightarrow1}{\frac{\frac{1-xe^{x-1}}{x}}{2(x-1)}}=\lim_{x\rightarrow1}{\frac{1-xe^{x-1}}{2x(x-1)}}=\lim_{x\rightarrow1}{h(x)}$$

Now,

$$h(x)\sim \frac{1-e^{x-1}}{2(x-1)}=\frac{-(e^{x-1}-1)}{2(x-1)}\sim\frac{-(x-1)}{2(x-1)}=-\frac 1 2$$

I think I did something wrong with the asymptotics because the solution is actually $-1$. Any hints?

$\endgroup$
3
$\begingroup$

You replaced $-xe^{x-1}$ by $-e^{x-1}$. The difference, $(1-x)e^{x-1}$ has the property that $\frac{(1-x)e^{x-1}}{2(x-1)}=-\frac{e^{x-1}}{2}\to -\frac12$ as $x\to 1$, which makes up for the shortfall in your solution.

$\endgroup$
1
$\begingroup$

As an alternative let $x-1=t \to 0$

$$\lim_{x\rightarrow1}{\frac{1+\log{x}-e^{x-1}}{(x-1)^2}}=\lim_{t\rightarrow0}{\frac{1+\log{(1+t)}-e^{t}}{t^2}}$$

then use the results indicated here to obtain

$$\frac{1+\log{(1+t)}-e^{t}}{t^2}=\frac{\log{(1+t)}-t}{t^2}-\frac{e^{t}-t-1}{t^2}\to -\frac12-\frac12=-1$$

Following your way from here we have

$$\lim_{x\rightarrow1}{\frac{\frac{1}{x}-e^{x-1}}{2(x-1)}}=\lim_{t\rightarrow0} {\frac{\frac{1}{1+t}-e^{t}}{2t}}$$

that is

$$\frac{\frac{1}{1+t}-e^{t}}{2t}=\frac{\frac{1}{1+t}-1+1-e^{t}}{2t}=-\frac1{2(1+t)}-\frac12\frac{e^t-1}{t} \to -\frac12-\frac12=-1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.